An investigation of the effect of tapered angle and boundary condition on natural frequency of different ceramic coated Ti-6Al-4V alloy with finite element analysis - Ergene, Berkay; Bolat, Çağın (Nigde Omer Halisdemir University, 2022)
In recent years, the interest in light metals has increased due to the increasing demand for components with high specific strength and long service life in the industry. In this context, titanium alloys have become very common and popular owing to their high strength/weight properties and superior refractory characteristics. In this study, the effect of boundary condition and tapered angle on the natural frequency and vibration behavior of the beam was investigated in Ti-6Al-4V beams coated with three different ceramic materials; Al2O3, AlN, and TiB2. Tapered angle values are considered as 0°, 0.2°, 0.4°, 0.6° and 0.8°. Besides, boundary conditions were evaluated in two conditions including left side fixed or both sides fixed. All analyzes were performed in the finite element-based Ansys APDL 19 program. According to the results obtained from the analyses, it was observed that there was a change in the natural frequency values according to the type of coating material, but no difference was found in terms of increase/decrease tendency. In addition, the resultant displacement values were determined for all samples. The results indicated that the resultant displacement values were severely affected by the tapered angle. A decreasing resultant displacement trend was observed in all samples with increasing tapered angle.

Son yıllarda sektörde özgül mukavemeti yüksek ve uzun ömürlü bileşenlere olan talebin artması nedeniyle hafif metallere olan ilgi artmıştır. Bu bağlamda titanyum alaşımları, yüksek mukavemet/ağırlık özellikleri ve üstün refrakter özellikleri nedeniyle oldukça yaygın ve popüler hale gelmiştir. Bu çalışmada, Al2O3, AlN ve TiB2 olmak üzere üç farklı seramik malzemesi ile kaplanmış Ti-6Al-4V kirişlerde sınır koşulunun ve konik açının kirişin doğal frekansı ve titreşim davranışına olan etkisi araştırılmıştır. Konik açı değerleri 0°, 0.2°, 0.4°, 0.6° ve 0.8° olarak ele alınmıştır. Ayrıca, sınır koşulları sol kenarın sabitlenmesi ya da her iki kenarın da sabitlenmesi olarak iki şekilde değerlendirilmiştir. Tüm analizler sonlu elemanlar bazlı Ansys APDL 19 programında gerçekleştirilmiştir. Analizlerden elde edilen sonuçlara göre, kaplama malzemesinin cinsine göre doğal frekans değerlerinde değişim olduğu ancak artış/azalma eğilimi açısından bir farklılık olmadığı görülmüştür. Ek olarak, tüm numuneler için bileşke deplasman değerleri belirlenmiştir. Sonuçlar, bileşke deplasman değerlerinin konik açıdan ciddi şekilde etkilendiğini göstermiştir. Konik açının artışı ile birlikte tüm numunelerin bileşke deplasman değerlerinde azalış eğilimi gözlemlenmiştir.
Keywords: Natural frequency; Ceramic coating; Tapered beam; Vibration behavior; Ti-6Al-4V; Mechanical Engineering; Vibration behavior; Doğal frekans; Seramik kaplama; Konik kiriş; Titreşim davranışı; Ti-6Al-4V; Makine Mühendisliği; Ceramic coating; Natural frequency; Ti-6Al-4V; Tapered beam